Combining Transition Metals – An Approach towards High-Performing Coking Tolerant Solid Oxide Fuel Cell Anodes. (10th July 2019) - Drasbæk, Daniel Bøgh; Traulsen, Marie Lund; Sudireddy, Bhaskar Reddy; Holtappels, Peter
Abstract : Bimetallic combinations of the three transition metals, Ni, Co, and Fe, were infiltrated alongside gadolinium doped ceria (CGO), into a strontium titanate backbone. The infiltrated cells were analyzed using electrochemical impedance spectroscopy in the temperature range 650°-850°C and in the atmospheres: 4% H2 O/H2, 50% H2 O/H2, 80% H2 O/H2, and 50% CO2 /CO. In addition, in situ synchronous Raman spectroscopy and EIS experiments were performed to explore the coking tolerance of the bimetallic infiltrations. The electrocatalytic activity of the bimetals were similar to the single metals with electrode area specific resistances 0.35 Ωcm 2, 0.28 Ωcm 2, and 1.32 of Ωcm 2 for the Co-Fe-CGO, Ni-Co-CGO, and Ni-Fe-CGO infiltrated cells, respectively, at 750 o C in 50% H2 O/H2 . The results obtained from the synchronous in situ Raman - EIS experiments further indicates an improved coking resistance for combined transition metal infiltrations.